A CASE SERIES: MICRO AND NANO FAT GRAFTING FOR THE TREATMENT OF TESSIER 3 AND 4 CRANIOFACIAL CLEFTS VOLUME DEFECT - Windura, Carolus Aldo; Soekamto, Tomie Hermawan; Fonny Josh (Jurnal Rekonstruksi dan Estetik, 2022)
HIGHLIGHTS: 1. Combination of micro and nano fat grafting shows promising results for correcting facial contour deformities caused by Tessier 3 and 4 craniofacial clefts.2. Nano fat grafting, which contains growth factors and stem cells, complements the properties of micro fat grafting, leading to increased survivability rate and better outcomes.   ABSTRACT: Background: Patients with craniofacial clefts who have had reconstructive surgery often develop problems, such as contour deformity that will cause psychological issues.  Micro and nano fat grafting are various methods utilized to overcome these issues. Case and Operation Technique: This case series describes two patients with facial contour deformities due to Tessier 3 and 4 craniofacial clefts, respectively.  Each patient underwent secondary reconstruction correction surgery followed by a combination of micro and nano fat grafting. Discussion: Results on day 7 after surgery were promising.  Growth factors and stem cells in nano fat complemented the micro fat properties, thus increasing the survivability rate. Conclusion: This case series demonstrates that the combination of micro and nano fat shows promising results for overcoming facial contour deformity.